Cervical Cancer Prevention Following A Cascade Strategy: Successes And Challenges - Idiovino, Rafael (My University, 2023)
The aim of this project has been to improve women’s access to cervical cancer prevention and care following a cascade strategy in Northern Mozambique. Results to date one dedicate examination room for VIA has been established; biopsies are possible now with analysis in Nampula; and LEEP is available on site now (equipment, health worker trained). Some challenges that should be addressed in future: what happen after 2nd referral? Can having an examination room integrated inside the HIV clinic improve screening and treatment uptake?
These activities are part of the project: Cervical Cancer Prevention and Care Cascade for women living with HIV in sub-Saharan Africa, that has received support from the Swiss Agency for Development and Cooperation; grant Advancing Cervical Cancer Screening in HIV-positive women (ACCHIVe) —The Cervical Cancer Prevention and Care Cascade (Award number: IZP8Z0_180245). The research is also supported by the Eunice Kennedy Shriver National Institute Of Child Health & Human Development (NICHD), National Institute Of Diabetes And Digestive And Kidney Diseases (NIDDK), National Heart, Lung, And Blood Institute (NHLBI), National Institute On Alcohol Abuse And Alcoholism (NIAAA), Fogarty International Center (FIC), National Cancer Institute (NCI), and by the National Institute of Allergy and Infectious Diseases of the National Institutes of Health under Award Number U01AI069924. We acknowledge the funding from the European Union’s Horizon 2020 research and innovation programme under the Marie Skodowska-Curie grant agreement No 801076 and support from the Federal Commission for Scholarships for Foreign Students for the Swiss Government Excellence Scholarship (ESKAS No. 2019.0741). The content is solely the responsibility of the authors and does not necessarily represent the official views of the funders.
Keywords: cervical cancer control; cervical cancer; cancer prevention